If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(3n+2)=2(13n-3)
We move all terms to the left:
7(3n+2)-(2(13n-3))=0
We multiply parentheses
21n-(2(13n-3))+14=0
We calculate terms in parentheses: -(2(13n-3)), so:We get rid of parentheses
2(13n-3)
We multiply parentheses
26n-6
Back to the equation:
-(26n-6)
21n-26n+6+14=0
We add all the numbers together, and all the variables
-5n+20=0
We move all terms containing n to the left, all other terms to the right
-5n=-20
n=-20/-5
n=+4
| 3x+9=5x-2+3 | | 28(x)=26 | | 2(4v-+7)=62 | | 3x+9=5x+1+3 | | Y=x^2+7x-16 | | -3y-5y*(y+4)=4 | | 2(4v-+7)=72 | | 10^x+3=100^x-2 | | 1/4(8x+12=15 | | 3y+25=71.5 | | -6x+10=2x-10 | | 6(x-6)=2(-2) | | 24°+2x+4=4x+2 | | 12x*8=331 | | 6x*8=331 | | x-1600=750 | | x=14+42 | | 6x*8=1080 | | 4/x+6–3/x-6=3x/x²-36 | | 4k^2-8k-9=0 | | 6x(8)=1080 | | 26+2x=-52+16x | | 6x=1080 | | 4y–20=44 | | g÷ 9/10= 8 | | 4x+-9=36 | | 4x-4+-9=36 | | 5−4/9x=2/3x−10 | | 5−49x=23x−10 | | 1(6x-6)-4=2(x+8) | | 11u-9+3u=-23 | | 8-p^2=-11 |